Peranan Gereja Katolik Dalam Penanganan Masalah Kekerasan Terhadap Perempuan Di Keuskupan Maumere Dan Larantuka, Flores, NTT - Robert Mirsel; Yosef keladu Koten; Ignasius Ledot (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
ABSTRACT:This article talks about the problem of violence against women in the Maumere and Larantuka dioceses, Flores, NTT and how religion (Catholic Church) functions in dealing with it. The aim is to identify the forms of violence, their causes and effects in both dioceses and what the function of religion (Catholic Church) is to prevent and deal with these problems. Interview methods, focused group discussions (FGD) and document studies were used to collect data, while descriptive qualitative analysis was used for data analysis. The results show that violence against women is found in both areas of the diocese with physical, psychological, verbal, economic, cultural-based and online violence. The Catholic Church through the Diocesan Commission on Gender and Women's Empowerment carries out educational, control, fraternal, and transformative functions. This is done in direct collaboration and through networks with multi-stakeholders, although this is not sufficient. This study recommends the importance of strengthening institutional capacity and increasing network collaboration. KEYWORDS: Commission on Gender and Women's Empowerment, institutional capacity, network collaboration, violence against women, women empowerment.